2022
DOI: 10.1155/2022/1537906
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Influencing Factors for Chronic Diseases: A Large Sample Epidemiological Survey from Liaoyang

Abstract: Purpose. Northeast China is a region with a serious aging population. There are fewer articles on epidemiological surveys on the prevalence of chronic diseases in aging areas of China. The study is aimed at understanding the prevalence of chronic noncommunicable diseases such as hypertension and diabetes mellitus (DM) in Liaoning Province, northeast China, and analyzing the risk factors for these chronic diseases. Methods. A questionnaire survey and physical examination were conducted in 5008 permanent residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…The results regarding the age effect, which is the effect of age on disease prevalence, were similar to those of previous studies, as the prevalence of NCDs was highest among older people, regardless of gender, urban versus rural regions, or famine intensity in the province (23)(24)(25). Similarly, the results in terms of gender were consistent with previous research showing a slightly higher prevalence of NCDs in females than males (26).…”
Section: Discussionsupporting
confidence: 90%
“…The results regarding the age effect, which is the effect of age on disease prevalence, were similar to those of previous studies, as the prevalence of NCDs was highest among older people, regardless of gender, urban versus rural regions, or famine intensity in the province (23)(24)(25). Similarly, the results in terms of gender were consistent with previous research showing a slightly higher prevalence of NCDs in females than males (26).…”
Section: Discussionsupporting
confidence: 90%
“…[2]. As DM is the problem of adaptation to treatment in chronic diseases prevents the success of treatment, it causes the disease process to progress negatively, other diseases and deaths to develop and the costs of the disease to increase [3]. Numerous easy-to-use and effective drugs for the treatment of DM in recent years low level of drug compliance in patients the effectiveness of clinical outcomes is limited.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%